Synthesis and characterization of polymeric thioxanthone photoinitatiors via double click reactions - Gacal, Burcin; Akat, Hakan; Balta, Demet K.; Arsu, Nergis; Yagci, Yusuf (AMER CHEMICAL SOC, 2008)
Macrophotoinitiators containing thioxanthone (TX) moieties as side chains were synthesized by using double click chemistry strategy; combining in-situ 1,3-dipolar azide-alkyne [3 + 2] and thermoreversible Diels-Alder (DA) [4 + 2] cycloaddition reactions. For this purpose, thioxanthone-anthracene (TX-A), N-proparayl-7-oxynorbornene (PON), and polystyrene (PS) with side-chain azide moieties (PS-N-3) were reacted in N,N-dimethylformamide (DMF) for 36 h at 120 degrees C. In this process, PON acted as a click linker since it contains both protected maleimide and alkyne functional groups Suitable for 1,3-dipolar azide-alkyne and Diels-Alder click reactions, respectively. This way, the aromacity of the central phenyl unit of the anthracene moiety present in TX-A was transformed into TX chromophoric groups. The resulting polymers possess absorption characteristics similar to the parent TX. Their capabilities to act as photoinitiator for the polymerization of mono-and multifunctional monomers, namely methyl methacrylate (MMA) and 1,1,1-tris(hydroxymethyl)propane triacrylate (TPTA) were also examined.
Keywords: FREE-RADICAL POLYMERIZATION; IN-CHAIN THIOXANTHONE; DIELS-ALDER REACTION; H-SHAPED TERPOLYMERS; EFFICIENT ROUTE; STAR POLYMERS; CHEMISTRY; PHOTOINITIATOR; COMBINATION; ATRP; Polymer Science